Chemotherapy Delays Are Associated with Inferior Outcome in Acute Lymphoblastic Leukemia: A Retrospective Study from a Tertiary Cancer Center in South India - Agrawal, Vineet; Kayal, Smita; Ganesan, Prasanth; Dubashi, Biswajit (Indian Journal of Medical and Paediatric Oncology, 2021)
Background Treatment protocols for acute lymphoblastic leukemia (ALL) have evolved over time to give excellent cure rates in children and moderate outcomes in adults; however, little is known how delays in chemotherapy affect long-term survival.Objectives To find the association of delays during different treatment phases on the survival outcomes.Materials and Methods Data from 149 ALL cases treated between 2009 and 2015 were retrospectively analyzed. Treatment course in commonly used protocols was divided into three phases—induction, consolidation (postremission), maintenance, and also a combined intensive phase (induction plus consolidation) for the purpose of analysis, and delay in each phase was defined based on clinically acceptable breaks. Analysis was done to find the impact of treatment delay in each phase on the survival outcomes.Results The median age was 12 years (range, 1–57). Multi-center Protocol-841 (MCP-841) was used for 72%, German Multicenter Study Group for Adult ALL (GMALL) for 19%, and Berlin, Frankfurt, Muenster, 95 protocol (BFM-95) for 9% of patients. Delay in induction was seen in 52%, consolidation in 66%, and during maintenance in 42% of patients. The median follow-up was 41 months, and 3-year survival outcomes for the entire cohort were event-free survival (EFS)—60%, relapse-free survival (RFS)—72%, and overall survival (OS)—68%. On univariate analysis, delay in induction adversely affected EFS (hazard ratio [HR] = 1.78, p = 0.04), while delay in intensive phase had significantly worse EFS and RFS (HR = 2.41 [p = 0.03] and HR = 2.57 [p = 0.03], respectively). On separate analysis of MCP-841 cohort, delay in intensive phase affected both EFS (HR = 3.85, p = 0.02) and RFS (HR = 3.42, p = 0.04), whereas delay in consolidation significantly affected OS with (HR = 4.74, p = 0.04) independently.Conclusion Treatment delays mostly in intensive phase are associated with worse survival in ALL; attempts should be made to maintain protocol-defined treatment intensity while adequately managing toxicities.
Keywords: acute lymphoblastic leukemia; delay; relapse; survival; treatment interruption